A School Mapping Research: The Areas for Junior High School Establishment in Cianjur based on Geographic Information System (GIS) - Ruhimat, Mochammad Devi Cahya; Kurniatun, Taufani C.; Permana, Johar; Shodikin, Rifan; Pradana, Rahadyan Surya (Indonesian Research Journal in Education |IRJE|, 2024)
This research recommends areas for establishing junior high schools in Cugenang, Pacet, and Cipanas (3 districts in Cianjur, Indonesia). It uses a descriptive quantitative. The spatial classification and analysis method with the Union feature Geographic Information System (GIS) overlay technique is applied – considering seven parameters: roads, slope, land use, population, fault, landslide danger, and earthquake danger. All of them are used as indicators to determine the suitability of the area. As a result, a map showing areas with five categories is created. Furthermore, in areas with very suitable categories, the researchers provide further testing with Satellite Imagery reviews to validate the coordinates of priority options. The researchers determined forty-nine priority option coordinates in nineteen villages and adapted these into a number script for user convenience. Supporting educational equality as one of the national priorities for 2030, the researchers are proposing these results.